Making ICT Decommissioning Sexy! Challenges and Opportunities - Hormann, Peter (Journal of Telecommunications and the Digital Economy, 2017)
The author contends that the ICT industry has become good at accumulating large inventories of ICT systems without paying sufficient attention to the associated technical debt and cost.  He has experienced organisations that have repeatedly failed to retire old systems, are struggling to modernise, are burdened by complexity and can’t change at a pace demanded by their internal stakeholders and their customers. Why is this case and why isn’t the decision to switch off ageing, low business value, poor strategic fit and high-risk systems an easy and obvious business case? This paper explores the challenges of decommissioning decision making and uses a framework and case study analysis as a means to improve the timeliness and financial motivations. It should be of interest to ICT and business executives that struggle with balancing a tight budget around existing systems, with the need to invest in systems modernisation to maintain organisation competitiveness and productivity.